2014
DOI: 10.1108/nlw-04-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Theses and dissertations in institutional repositories: an Asian perspective

Abstract: Purpose – Institutional repositories constitute an integral part of present day digital libraries allowing global access to scholarly publications and provides an opportunity for future research enhancement and long term preservation of information. Electronic theses and dissertations (ETDs) represent a growing segment of available content in institutional repositories where they contribute to the impact and ranking of their institutions. The present study traces the growth and development of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Majority of the IRs are functional in nature except for Afghanistan (Table III). Operational status in the majority of the repositories has also been ascertained by Abrizah et al (2010), Ahmed et al (2014), Ali et al (2013), Loan and Sheikh (2016), Singh (2016) and Wani et al (2009).…”
Section: Operational Statusmentioning
confidence: 87%
See 3 more Smart Citations
“…Majority of the IRs are functional in nature except for Afghanistan (Table III). Operational status in the majority of the repositories has also been ascertained by Abrizah et al (2010), Ahmed et al (2014), Ali et al (2013), Loan and Sheikh (2016), Singh (2016) and Wani et al (2009).…”
Section: Operational Statusmentioning
confidence: 87%
“…They also found that majority of the repositories are "institutional" in nature with English as dominating content language and "DSpace" as the prioritized content management software. Ahmed et al (2014) "trace the growth and development of online e-theses repositories in Asia and reveal that the growth pattern is on increase with Japan, India, and China among the top contributors. "English" stays the preferred content language with majority of the repositories, operational in nature.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Clement (n.d.) has also published on the number of institutions dropping their requirements for students to submit their dissertations to ProQuest in favor of their own institutional repositories, and has noted elsewhere that ProQuest's holdings of dissertations have always been incomplete (Clement, 2013). Other articles examined the number of IRs with ETDs in Asian countries (Ahmed, Alreyaee, & Rahman, 2014) or usage of ETDs by in-state or out-of-state users (Coates, 2014). While these articles take for granted the assumed benefits of OA theses and dissertations, some earlier pieces expressly make the case for their value, arguing against potential objections.…”
Section: Literature Reviewmentioning
confidence: 99%